Patterns of Neuropsychological Dysfunction and Cortical Volume Changes in Logopenic Aphasia. - Owens, Tyler E; Machulda, Mary M; Duffy, Joseph R; Strand, Edythe A; Clark, Heather M; Boland, Sarah; Martin, Peter R; Lowe, Val J; Jack, Clifford R; Whitwell, Jennifer L; Josephs, Keith A (J Alzheimers Dis, 2018)
BACKGROUND: Neuropsychological assessment can add essential information to the characterization of individuals presenting with the logopenic variant of primary progressive aphasia (lvPPA). OBJECTIVE: This study examined the neuropsychological characteristics of lvPPA patients. We also examined differences in regional and whole brain atrophy based on neuropsychological profiles. METHODS: We conducted a hierarchical cluster analysis on memory, executive functioning, and visuospatial neuropsychological test data for 56 individuals with lvPPA. We then compared resultant clusters to left middle temporal, inferior parietal, and superior parietal regions-of-interest using multivariate analysis of covariance. We also performed voxel-level analyses. RESULTS: We identified three clusters characterized as lvPPA with no neurocognitive impairment (n = 5), lvPPA with mild neurocognitive deficits (n = 23), and lvPPA with marked cognitive deficits (n = 28). WAB-AQ was associated with left middle temporal volume. Superior parietal volumes were smaller for the lvPPA group with marked cognitive symptoms compared to the less severe groups. Voxel-level analyses showed greater atrophy in temporal, parietal, lateral occipital, and frontal regions, left worse than right. Age, disease duration, gender, WAB-AQ, and PiB-PET did not account for differences between groups. CONCLUSIONS: LvPPA patients without cognitive deficits in other domains were relatively uncommon while 50% of our sample exhibited pronounced neurocognitive deficits outside the language domain. Pronounced cognitive deficits in lvPPA are associated with widespread atrophy, left worse than right. Our study underscores the importance of examining neuropsychological function in addition to language in patients with lvPPA.

Varying Degrees of Temporoparietal Hypometabolism on FDG-PET Reveal Amyloid-Positive Logopenic Primary Progressive Aphasia is not a Homogeneous Clinical Entity. - Krishnan, Kamini; Machulda, Mary M; Whitwell, Jennifer L; Butts, Alissa M; Duffy, Joseph R; Strand, Edythe A; Senjem, Matthew L; Spychalla, Anthony J; Jack, Clifford R; Lowe, Val J; Josephs, Keith A (J Alzheimers Dis, 2017)
BACKGROUND: The logopenic variant of primary progressive aphasia (lvPPA) manifests due to a breakdown of the language network with prominent hypometabolism of the left temporoparietal region. LvPPA is strongly associated with amyloid deposition, yet there is question as to whether it is a homogeneous clinical entity. OBJECTIVE: This study investigated whether differences in temporoparietal metabolic patterns on 18F fludeoxyglucose positron emission tomography (FDG-PET) could elucidate brain regions preferentially affected in lvPPA. METHOD: We used differences in FDG-PET metabolic z-scores relative to controls for means of left lateral temporal, left inferior parietal, and left superior parietal regions to classify 53 amyloid-positive lvPPA patients into temporal, parietal, or temporoparietal predominate groups. Clinical features and FDG-PET regions of hypometabolism outside of the temporoparietal region were then compared across the three groups; the latter using statistical parametric mapping. RESULTS: Of the 53 lvPPA patients, 15 were classified as temporal, 14 as temporoparietal, and 22 as parietal predominate. There were no significant differences between the groups on demographic measures, language evaluation, or apolipoprotein E genotype. Compared to the other two groups, individuals with the parietal predominate pattern had extensive hypometabolism in left frontal lobe and the precuneus. Furthermore, this group had greater behavioral dyscontrol and deficits in executive function, visuospatial skills, visual memory retention, working memory, and cognitive flexibility (Bonferronip < 0.05). CONCLUSIONS: This study demonstrates that there is clinical heterogeneity within amyloid-positive lvPPA. Patients with lvPPA with predominant parietal hypometabolism, unlike those with temporal or temporoparietal predominant hypometabolism, demonstrated widespread cognitive and behavioral changes.

Characterizing White Matter Tract Degeneration in Syndromic Variants of Alzheimer's Disease: A Diffusion Tensor Imaging Study. - Madhavan, Ajay; Schwarz, Christopher G; Duffy, Joseph R; Strand, Edythe A; Machulda, Mary M; Drubach, Daniel A; Kantarci, Kejal; Przybelski, Scott A; Reid, Robert I; Senjem, Matthew L; Gunter, Jeffrey L; Apostolova, Liana G; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Different clinical syndromes can arise from Alzheimer's disease (AD) neuropathology, including dementia of the Alzheimer's type (DAT), logopenic primary progressive aphasia (lvPPA), and posterior cortical atrophy (PCA). OBJECTIVE: To assess similarities and differences in patterns of white matter tract degeneration across these syndromic variants of AD. METHODS: Sixty-four subjects (22 DAT, 24 lvPPA, and 18 PCA) that had diffusion tensor imaging and showed amyloid-β deposition on PET were assessed in this case-control study. A whole-brain voxel-based analysis was performed to assess differences in fractional anisotropy, mean diffusivity, axial diffusivity, and radial diffusivity across groups. RESULTS: All three groups showed overlapping diffusion abnormalities in a network of tracts, including fornix, corpus callosum, posterior thalamic radiations, superior longitudinal fasciculus, inferior longitudinal fasciculus, inferior fronto-occipital fasciculus, and uncinate fasciculus. Subtle regional differences were also observed across groups, with DAT particularly associated with degeneration of fornix and cingulum, lvPPA with left inferior fronto-occipital fasciculus and uncinate fasciculus, and PCA with posterior thalamic radiations, superior longitudinal fasciculus, posterior cingulate, and splenium of the corpus callosum. CONCLUSION: These findings show that while each AD phenotype is associated with degeneration of a specific structural network of white matter tracts, striking spatial overlap exists among the three network patterns that may be related to AD pathology.
Keywords: Aged; Alzheimer Disease; Aniline Compounds; Anisotropy; Aphasia, Primary Progressive; Case-Control Studies; Diffusion Tensor Imaging; Female; Humans; Image Processing, Computer-Assisted; Male; Middle Aged; Nerve Fibers, Myelinated; Neurodegenerative Diseases; Neuropsychological Tests; Positron-Emission Tomography; Psychiatric Status Rating Scales; Retrospective Studies; Thiazoles; White Matter